1982
DOI: 10.1180/claymin.1982.017.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Supergene alteration of metamorphic chlorite in an amphibolite from Massif Central, France

Abstract: The mineralogical and chemical changes of sheridanite were followed in different alteration horizons as weathering of its host amphibolite increased. Microscopic and microprobe analyses of phases produced in or around the chlorite allowed a classification of the different alteration stages relative to their position in the profile. In the unweathered rock, prehnite and a sericite—kaolinite assemblage appear to have formed at grain boundaries between chlorites and plagioclases. These represent low-pressure (PH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Previous petrographic studies of naturally weathered pyriboles have noted what appeared to be early-stage weathering products in fractures and cleavages (see, e.g., Basham, 1974;Cleaves, 1974;Colman, 1982;Proust, 1982Proust, , 1985. Alteration apparently originated at grain boundaries and intragranular fractures and grew inward to the present contact.…”
Section: Previous Workmentioning
confidence: 86%
“…Previous petrographic studies of naturally weathered pyriboles have noted what appeared to be early-stage weathering products in fractures and cleavages (see, e.g., Basham, 1974;Cleaves, 1974;Colman, 1982;Proust, 1982Proust, , 1985. Alteration apparently originated at grain boundaries and intragranular fractures and grew inward to the present contact.…”
Section: Previous Workmentioning
confidence: 86%
“…The samples were generally from basic rocks which had been exposed to supergene conditions (Veniale and van der Marel, 1963;Kanno et al, 1965;Wildman et al, 1968Wildman et al, , 1971Ducloux et al, 1976;Garcia and Delgado, 1978;Wilson and Berrow, 1978;Istok and Harward, 1982;Proust, 1982) and diagenetic or metamorphic conditions (April, 1980;Curtis et al, 1985). Experimental transformations among these phases have also been reported Kodama,-1974, 1976;Senkayi et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies leave some ambiguity about the origin of mixed-layered chlorite/vermiculite or chlorite/smecrite and hydroxy-interlayered vermiculite or smectite, all of which may be found in the weathered products. Many authors have suggested that dehydroxylarion of chlorite leads to mixed-layer materials showing vermiculitic or smecriric properties (Veniale and van der Marel, 1963;Garcia and Delgado, 1978;Senkayi et al, 1981;Proust, 1982). (The terms vermiculitic and smecritic are used here to avoid discussion about the interpretation of X-ray powder diffractograms of such mixed-layer materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vermiculitic phases have been previously interpreted to have formed from chlorite, either during weathering or retrograde metamorphism (e.g., Johnson 1964, Brown 1967, Proust 1982, Proust et al 1986, Banfield & Murakami 1988, Murakami et al 1996, or during prograde metamorphism (e.g., Kerrick & Cotton 1971, Velde 1978, Maresch et al 1985. In the Maláguide rocks, textural, chemical and structural evolution with increasing metamorphic conditions indicate that most of these phases formed during prograde Alpine metamorphism (Ruiz Cruz 1999, 2001).…”
Section: Introductionmentioning
confidence: 99%